Notice of a Notarial Instrument, narrating the Proceedings on the Election of Janet Hoppringil as Prioress of Coldstream, on 23d February 1537-8 (Proceedings of the Society of Antiquaries of Scotland, 1865)
This article describes the process by which the nuns of Coldstream Priory selected a new Prioress after the death of the previous Prioress, Isabella Hoppringle. Some information about the the Priory and the original Latin text of the Prioress' election was also included.